Prediction of ADHD symptoms from prenatal data in two large population-based cohorts - N. Dooley; M. Cannon; D. Cotter; M. Clarke (European Psychiatry, 2022)
Introduction The association between low birth weight and attention problems in childhood has been replicated many times (e.g. Momany, Kamradt, & Nikolas, 2018). However birth weight is unlikely the aetiological start-point of this association, as birth weight is itself the product of many prenatal factors e.g. gestational complications, maternal toxin exposure during pregnancy and basic demographics.